All-polymer waterproof triboelectric nanogenerator towards blue energy harvesting and self-powered human motion detection. (15th May 2022) - Win Zaw, Nay Yee; Yun, Jonghyeon; Goh, Tae Sik; Kim, Inkyum; Kim, Youngsu; Lee, Jung Sub; Kim, Daewon
Abstract: With growing energy crisis in this era, developing and utilizing sustainable energy sources are required because the conventional energy sources cannot be restored. Among the various sustainable energy sources, the ocean wave energy is considered as one of the best sustainable energy sources. However, the conventional technologies to harvest the ocean energy show some limitations such as corrosion. Hence, guaranteeing the high resistance to corrosion of the harvesting devices has become a critical challenge for ocean-energy harvesting. Herein, a mat-shaped solid-liquid triboelectric nanogenerator is fabricated to harvest the blue energy while overcoming the shortcomings of the conventional technologies. The fabricated device is composed of the polydimethylsiloxane embedded in a conductive carbon black utilized as the electrode of the proposed device and it can directly harvest the blue energy. Moreover, through acquired energy from the simulated waves, the fabricated device can operate an anemometer and can split the seawater to produce the hydrogen. Also, the human motions can be distinguished through the k-mean clustering method with the high classification of 96.67%. Considering these results, the fabricated device is expected to be utilized as the promising blue energy harvester as well as the self-powered human motion sensor in near future. Graphical abstract: Image 1 Highlights: A mat-shaped solid-liquid triboelectric nanogenerator (MSLT) was fabricated. The MSLT can harvest the blue energy and mechanical energy, respectively. Also, the MSLT showed great a potential as a human motion detecting sensor. Self-powered water splitting system can be implemented with the fabricated MSLT.